PEMANFAATAN ABU VULKANIK GUNUNG KELUD SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS PADA BETON NORMAL SEBAGAI PENDUKUNG BAHAN AJAR MATA KULIAH TEKNOLOGI BETON (PADA MAHASISWA PTB, JPTK, UNS) - Abdul Rohman Anshory; Sri Sumarni; Roemintoyo Roemintoyo (Universitas Sebelas Maret, 2015)
The purpose of this study was to determine (1) Effect of volcanic ash in partial replacement of the total fine aggregate of compressive strength and the density of the concrete, (2) resistance to theoptimal scatter hitam compression of the concrete (3) optimum density concrete. (4) The teaching material obtained inthe course of concrete technology on the effect of volcanic ash on the compressive strength of concreteand normal density. Experimental studies using methods and analytical techniques using a quantitativeanalysis of regression. Variables in the study were (1) the dependent variable: the strength of concrete incompression and the density of concrete, (2) independent variables: the variation of 0%, 10%, 15%, 20%and 25% Volcanic ash from the total weight of the sand. The sampel is in the form of a cylinder with adiameter of 150 mm and a height of 300 mm. Based on the results of the study concluded that (1) changesin volcanic ash as a partial replacement of the fine aggregate strong overall influence on the compressivestrength and density of concrete, (2) the optimal value of compressive strength and the weight of eachtype of concrete which is the variation of volcanic ash 8,36% amounted to 23,231 MPa, 11,889% to22,919 MPa, (3) the value of the optimal concrete mixture as a whole, to namely the variation of volcanicash 11,889% (4) in the form of teaching material to supplement teaching materials using Kelud volcanicash as a partial replacement of fine aggregate on in terms of compressive strength concrete and density.Key words: normal concrete, volcanic ash, compressive strength, density